SARS-CoV-2 Neutralization Assay System using Pseudo-lentivirus - Anastasia Armimi; Afina Firdaus Syuaib; Katherine Vanya; Marselina Irasonia Tan; Dessy Natalia; David Virya Chen; Chikako Ono; Yoshiharu Matsuura; Anita Artarini; Ernawati Arifin Giri-Rachman (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infects humans' lower respiratory tracts and causes coronavirus disease-2019 (COVID-19). Neutralizing antibodies is one of the adaptive immune system responses that can reduce SARS-CoV-2 infection. This study aimed to develop a SARS-CoV-2 neutralization assay system using pseudo-lentivirus.METHODS: The plasmid used for pseudo-lentivirus production was characterized using restriction analysis. The gene encoding for SARS-CoV-2 spike protein was confirmed using sequencing. The transfection pseudo-lentivirus optimal condition was determined by choosing the transfection reagents and adding centrifugation step. Optimal pseudo-lentivirus infection was analysed using fluorescent assay and luciferase assay. The optimal condition of pseudo-lentivirus infection was determined by the target cell type and the number of pseudo-lentiviruses used for neutralization test. SARS-CoV-2 pseudo-lentivirus was used to detect neutralizing antibodies from serum samples.RESULTS: The plasmid used for pseudo-lentivirus production was characterized and confirmed to have no mutations. Lipofectamine 2000 reagent generated pseudo-lentivirus with a higher ability to infect target cells, as indicated by a percentage green fluorescent protein (GFP) of 12.68%. Pseudo-lentivirus centrifuged obtained more stable results in luciferase expression. Optimal pseudo-lentivirus infection conditions were obtained using puromycin-selected HEK 293T-ACE2 cells as target cells. The number of pseudo-lentiviruses used in the neutralization assay system was multiplicity of infection (MOI) 0.075. Serum A samples with a 1:10 dilution had the highest neutralizing antibody activity.CONCLUSION: This study shows that SARS-CoV-2 neutralization assay system using pseudo-lentivirus successfully detected neutralizing antibodies in human serum, which were indicated by a decrease in the percentage of pseudo-lentivirus infections.KEYWORDS: COVID-19, neutralizing antibody, neutralization assay, pseudo-lentivirus, SARS-COV-2